Migration and Social Pathways Biographies of Highly Educated People Moving East-West-East in Europe - Guhlich, Anna (Verlag Barbara Budrich, 2017)
The landscape of European migration has changed considerably over the past decades, in particular after the fall of the iron curtain and again after the EU enlargement to the east. The author researches the phenomenon of highly qualified migration using the example of migration between the Czech Republic and Germany. The book reveals diverse strategies migrants use to respond to the possible de-valuation of their qualification, e.g. by making use of their language skills, starting new studies or using transnational knowledge.Anna Guhlich investigates the role of migration within the biographies, the shifts of social positions, as well as the ways migrants negotiate their skills, qualification and knowledge across the borders. Based on biographical narrative interviews, she investigates the migration pathways and the processes of social mobility. The study investigates the influence developments within the Czech society have on migration decisions and transnational spaces as well as o